Impact of Brand Image and Corporate Branding on Customer’s Choice: A Case of Commercial Banks in Kathmandu Valley - Paudel, Shreeyasi; Pradhan, Radhe Shyam (Nepalese Journal of Management, 2024)
This study examines the impact of brand image and corporate branding on customer’s choice of commercial banks in Kathmandu Valley. Customer choice is the selected dependent variable. The selected independent variables are brand preferences, brand value, brand loyalty, brand image and brand trust. The primary source of data is used to assess the opinions of the respondents regarding brand image and corporate branding of Nepalese commercial banks. The study is based on primary data with 150 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of brand image and corporate branding on the customer’s choice of commercial banks in Kathmandu Valley. The study showed that brand image has a positive effect on customer’s choice. It indicates that better brand image of the bank stimulates the behavior of customer to choose the specific bank. Similarly, brand preference has a positive impact on customer’s choice. It indicates that better brand preference drives the behavior of customer to choose the specific bank. Likewise, brand trust has a positive impact on customer’s choice. It indicates that increase in brand trust stimulates the behavior of customer to choose the specific bank. Similarly, brand value has a positive impact on customer’s choice indicating that higher brand value drives the behavior of customer to choose the specific bank. Furthermore, brand loyalty has a positive impact on customer’s choice indicating that higher brand loyalty stimulates the behavior of customer to choose the specific bank.